2018
DOI: 10.5070/l210235331
|View full text |Cite
|
Sign up to set email alerts
|

Textual Borrowing and Perspective-Taking: A Genre-Based Approach to L2 Writing

Abstract: This qualitative study explored the impact of reading on writing in a collegiate French culture course that emphasized genre-based writing pedagogy. In particular, the study focused on how 19 advanced collegiate learners of French used model text resources in writing a letter-manifesto and what their perceptions were of participation in genre-based writing instruction. Based on this study's findings, the authors make an argument for how genre-based pedagogy can facilitate advanced literacy development in a FL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The findings of a study conducted by Morell and Cesteros (2019) confirmed that GBI of writing positively affects genre knowledge and genre awareness of bilingual applied linguistic students. In a qualitative study, Allen and Goodspeed (2018) employed GBI pedagogy and approved that GBI pedagogy facilitated the literacy development of 19 advanced collegiate learners of French writing courses. The findings confirmed that genre knowledge had positive effects o the accomplishment of research writing.…”
Section: │ 119mentioning
confidence: 99%
“…The findings of a study conducted by Morell and Cesteros (2019) confirmed that GBI of writing positively affects genre knowledge and genre awareness of bilingual applied linguistic students. In a qualitative study, Allen and Goodspeed (2018) employed GBI pedagogy and approved that GBI pedagogy facilitated the literacy development of 19 advanced collegiate learners of French writing courses. The findings confirmed that genre knowledge had positive effects o the accomplishment of research writing.…”
Section: │ 119mentioning
confidence: 99%
“…Given such purposes for writing, instructors might include a much broader variety of specific genres within beginning courses; focus entire courses on a particular genre, for example, narrative, expository, or persuasive writing; and explore a variety of approaches to feedback that speak directly to the purpose for writing in a given context and to the students' particular motivations for writing in the target language. (For more on genre in non‐English L2 writing, see, e.g., Abdel‐Malek, ; Allen & Goodspeed, ; Byrnes, ; Maxim, . )…”
Section: Purposes For Writingmentioning
confidence: 99%
“…Researchers have investigated the implementation of multiliteracies pedagogy in lower-level L2 Journal Vol. 11 Issue 1 (2019) 36 collegiate Spanish curriculum (Menke & Paesani, 2018), in a university-level advanced French grammar course that emphasized reading-writing connections (Paesani, 2016), by non-tenure track faculty (Menke, 2018), via engagement with authentic literary texts (Blyth, 2018;Thoms & Poole, 2018), and within genre-based approaches to L2 writing (Allen & Goodspeed, 2018), to name just a few examples. However, little attention has been paid to peer response.…”
Section: _______________mentioning
confidence: 99%
“…Paesani (2018) notes the German Department at Georgetown, the German curriculum at Emory University, and the French program at Wayne State as three noteworthy models of literacies-based collegiate foreign language curricula. See alsoAllen and Goodspeed's (2018) work at the University of Wisconsin-Madison.…”
mentioning
confidence: 99%